Approximation of Burger's Equation Using Sextic B-Spline Galerkin Scheme with Quintic Weight Function (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this study, We produce the new numerical scheme which relies on sextic B-spline Galerkin method takes with quintic B-spline as a weight function, for solving the Burger's equation, contrasted  with exact solution can be done and then we find out a linear stability analysis which is erect on a Fourier (Von Neumann) method.